Severe Ketoacidosis Associated with Canagliflozin (Invokana): A Safety Concern. (21st March 2016) - Gelaye, Alehegn; Haidar, Abdallah; Kassab, Christina; Kazmi, Syed; Sinha, Prabhat
Abstract : Canagliflozin (Invokana) is a selective sodium glucose cotransporter-2 (SGLT-2) inhibitor that was first introduced in 2013 for the treatment of type 2 diabetes mellitus (DM). Though not FDA approved yet, its use in type 1 DM has been justified by the fact that its mechanism of action is independent of insulin secretion or action. However, some serious side effects, including severe anion gap metabolic acidosis and euglycemic diabetic ketoacidosis (DKA), have been reported. Prompt identification of the causal association and initiation of appropriate therapy should be instituted for this life threatening condition.